2020
DOI: 10.1111/ijfs.14570
|View full text |Cite
|
Sign up to set email alerts
|

Steam‐assisted roasting inhibits formation of heterocyclic aromatic amines and alters volatile flavour profile of beef steak

Abstract: SummaryIn order to evaluate the effect of steam addition during meat roasting, beef sirloin steaks were cooked at five humidities (0%, 25%, 50%, 75% and 100%) under 230 °C to a centre temperature of 71 °C. With increased humidity, heating rate generally increased and the cooked steak gradually lost the typical roasted appearance. Thiobarbituric acid‐reactive substances (TBARS) values generally increased, while carbonyl groups were not affected. Increased humidity promoted the formation of volatile aldehydes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Although other authors observed in horse meat that this compound is the most abundant [ 25 , 54 ], they observed a different trend during the vacuum aging, showing increasing values. These compounds also derive from lipid oxidation, particularly from the degradation of oleic and linoleic acid [ 69 ], and their liberation depends on thermal treatment [ 70 ]. The absence of variation can be due to a probable inhibition of the oxidation processes during the vacuum aging.…”
Section: Discussionmentioning
confidence: 99%
“…Although other authors observed in horse meat that this compound is the most abundant [ 25 , 54 ], they observed a different trend during the vacuum aging, showing increasing values. These compounds also derive from lipid oxidation, particularly from the degradation of oleic and linoleic acid [ 69 ], and their liberation depends on thermal treatment [ 70 ]. The absence of variation can be due to a probable inhibition of the oxidation processes during the vacuum aging.…”
Section: Discussionmentioning
confidence: 99%
“…However, cooking can adversely affect the quality and safety of meat and meat products, especially when it is not performed appropriately. The formation of heterocyclic aromatic amines (HAAs), which are highly hazardous to human health, is one of these negative changes that occur as a result of the thermal processing of meat (Feng et al., 2020; Oz, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Acetaldehyde, which has a fresh or green aroma descriptor, was higher for THIN compared with THICK (P = 0.030). Some of these aldehydes are a result of lipid degradation, which would naturally be higher at lower time and grill temperature, resulting in more moisture being on the surface, resulting in their higher concentration (Feng et al, 2020). Dodecane (floral or fragrant aroma; Kerth and Miller, 2015) and undecane values were higher for steaks cooked at a grill temperature of HIGH compared with LOW, but heptane values were higher for steaks cooked at LOW compared with those cooked at HIGH (P = 0.002, 0.001, 0.018, respectively).…”
Section: Volatile Aroma Compoundsmentioning
confidence: 99%